2017
DOI: 10.22159/ajpcr.2017.v10i4.16582
|View full text |Cite
|
Sign up to set email alerts
|

IN VITRO STUDY OF URSOLIC ACID COMBINATION FIRST-LINE ANTITUBERCULOSIS DRUGS AGAINST DRUG-SENSITIVE AND DRUG-RESISTANT STRAINS OF Mycobacterium tuberculosis

Abstract: Objective: The resurgence of tuberculosis (TB) caused by Mycobacterium TB (MTB) is associated with the rapid spread of multidrug-resistant, therefore, the development of new antimycobacterial agents is necessary. The aim of this study was to evaluate the antimycobacterial activity of ursolic acid (UA) when it using alone and combination with TB drugs.Methods: MTB H37Rv strain, streptomycin-rifampicin resistant strain, and isoniazid-ethambutol resistant strain were evaluated by susceptibility test using a seria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…It reported having a wide range of activities including anti mycobacteria and can inhibit the growth of MTB in both sensitive and resistant strains. It also is shown that UA has a synergistic effect when it combined with INH, rifampicin, ethambutol, or pyrazinamide [13]. In this research, UA acts as a ligand and docked on the site of drug action of the selected receptor of MTB which is responsible for the pharmaceutical effect.…”
Section: ■ Results and Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…It reported having a wide range of activities including anti mycobacteria and can inhibit the growth of MTB in both sensitive and resistant strains. It also is shown that UA has a synergistic effect when it combined with INH, rifampicin, ethambutol, or pyrazinamide [13]. In this research, UA acts as a ligand and docked on the site of drug action of the selected receptor of MTB which is responsible for the pharmaceutical effect.…”
Section: ■ Results and Discussionmentioning
confidence: 78%
“…In vitro study of UA found that it has activity as anti-TB with Minimum Inhibitory Concentration (MIC) in sensitive and resistant strains of MTB. UA has also displayed a synergistic interaction when combined with isoniazid (INH), rifampicin, ethambutol, and streptomycin [13]. The in vivo study was also found that UA showed a significant reduction of activity in rats induced by MTB H37Rv sensitive strain and MDR strains [14].…”
Section: ■ Introductionmentioning
confidence: 94%
“…In 2017, 87% of new TB cases occurred in 30 countries and >95% cases of TB-infected individuals in developing countries such as India, China, Indonesia, the Philippines, Pakistan, Nigeria, Bangladesh, and South Africa [2]. Indonesia, with 842,000 cases, is the third country with the highest number of cases of TB worldwide after India and China [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The compliance with medication intake in patients infected with TB and with other diseases is challenging, leading to multidrug-or rifampicin-resistant (RR) TB (Multidrug resistance [MDR]/RR-TB) [4,5]. Some reasons for this include failure in dose use, indiscipline, and drug interaction with other medicines [6].…”
Section: Introductionmentioning
confidence: 99%
“…Angiogenesis was highly needed by tumor cells to spread to another organ or metastatic [12]. Ursolic acid was able to inhibit the regulation of pro-inflammatory cytokines expression through the inhibition of NF-κB activation and antitumor [13]. In the other hand, TCa contains diterpenoid compounds that exhibit cytotoxic activities in human prostate cancer [14].…”
Section: Introductionmentioning
confidence: 99%